The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1163/156856101300157524
|View full text |Cite
|
Sign up to set email alerts
|

The influence of porosity and morphology of hydrated oxide films on epoxy-aluminium bond durability

Abstract: Clad aluminium alloy was pretreated by immersion in boiling water for times ranging between 30 s and 4 h. The chemical and physical properties of the lms produced in the 100 ± C water were characterized by techniques including X-ray photoelectron spectroscopy (XPS), Rutherford backscattering spectroscopy (RBS), scanning electron microscopy (SEM), and secondary ion mass spectrometry (SIMS). The durability of the bonds formed between the boiling water lms and a rubber-toughened epoxy adhesive was assessed in ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 21 publications
(26 reference statements)
1
14
0
1
Order By: Relevance
“…At 2-minute immersion time, only the weak peak at 3420 cm -1 was seen. As the immersion time increased, the 3420 cm -1 peak shifted to 3300 cm -1 and the shoulder moved into a peak at 3100 cm -1 [21]. ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…At 2-minute immersion time, only the weak peak at 3420 cm -1 was seen. As the immersion time increased, the 3420 cm -1 peak shifted to 3300 cm -1 and the shoulder moved into a peak at 3100 cm -1 [21]. ( Fig.…”
Section: Resultsmentioning
confidence: 91%
“…The vapour pressure of the steam is high at high temperature, which resulted in the higher thickness of the oxide. The initial growth of the oxide was higher due to the diffusion and dissolution mechanism explained by many researchers in literature [27,34,35]. However with the increase in thickness of the oxide layer, rate control shifts to the diffusion of H + through the steam generated oxide film which results in the higher oxide thickness for short time treatment as compared to 10 min.…”
Section: Discussionmentioning
confidence: 98%
“…Alwitt [10] reported that in the range of 100-374°C the only oxide phase existing is boehmite under hydrothermal or steam conditions, which is in agreement with the present findings. The mechanism of oxide film growth from aluminium and water reaction has been extensively studied [25][26][27]. The reaction between aluminium and water/water vapour results in the formation of amorphous hydrous oxide film [10].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of hydroxyl group is an important aspect due to the possibility of forming bonds by donating negatively charged oxygen [24]. Rider [25] reported that adhesion and durability of applied epoxy coating was affected by boiling water treatment of aluminium. Strålin and Hjertberg [26] found that the adhesion of ethylene vinyl acetate polymer with a pseudo-boehmite aluminium oxyhydroxide layer is stronger than with a dehydroxylated aluminium oxide.…”
Section: Introductionmentioning
confidence: 99%